The influence of systematic risk and liquidity on stock return at mining sector companies - Wildan Hidayatullah; Gusganda Suria Manda (The Accounting Journal of Binaniaga, 2021)
The purpose of this research is to examine the influence of systematic risk and liquidity on stock return at mining sector companies listed in Indonesia Stock Exchange (IDX) from 2017 to 2019. The analysis method used by the author is verification by collecting data from Indonesia Stock Exchange website and Yahoo Finance. The sampling technique used is purposive sampling. This research involves 32 mining sector companies on the Indonesia Stock Exchange. The Systematic risk variable is measured by beta and the liquidity variable measured by the current ratio. Multiple linear regression, simultaneous and partial regression is the data analysis techniques used in this research. The result of this study shows that systematic risk and liquidity simultaneously have a significant influence on stock return. Systematic risk has a negative and significant impact on the stock return and liquidity has a positive and insignificant impact on the stock return. Keywords: Systematic Risk, Liquidity, Stock Return.